Promoting Eco-Friendly Consumption Behavior in Vocational High School Students: A Comprehensive Case Study of Educational Approaches - Sri Handayani; Forijati Forijati; Subagyo Subagyo (Knowledge Dynamics, 2024)
Background: Students can be taught eco-friendly consuming habits through classroom learning activities with the help of teachers and other school-related activities. The study's focus is a case study completed at a vocational high school. We seek to understand the broad-reaching consequences that this teaching strategy might evoke by examining the potential implications of integrating environmentally responsible consumption practices within an educational framework. Through a thorough case study, we aim to shed light on how incorporating environmentally responsible consuming practices into schooling could support more general educational goals and encourage sustainable habits. Internalizing this through character education entails setting models and developing routine behaviors based on school policies and extracurricular activities in addition to integrated environmental education. This supports the long-term integration of these ideals into students' personalities. Method: This research uses a survey methodology and is explanatory. The SPSS (Statistical Package for Social Science) was used to analyze the data. 95 respondents make up the sample size for the sampling method, which uses proportionate random sampling. Result: According to the research's findings, integrating character education and general education are impacted by internalizing environmentally responsible consumption habits.